2020
DOI: 10.1039/d0cp00347f
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the catalyst chemical state and adsorbed species during methanol conversion on copper using ambient pressure X-ray spectroscopies

Abstract: A model Cu catalyst surface oxidises to Cu2O when methanol, oxygen and water vapour are all present during methanol conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It will cast light on the debated topic by gaining a fundamental insight into molecular behavior at the interface. However, several major challenges about operando techniques are constantly raised because of the poor reliability of data acquisitions by contamination or beam damage effect during experiments. , Therefore, there is plenty of room for exploration in operando surface chemistry for a robust foundation of future heterogeneous catalysis.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…It will cast light on the debated topic by gaining a fundamental insight into molecular behavior at the interface. However, several major challenges about operando techniques are constantly raised because of the poor reliability of data acquisitions by contamination or beam damage effect during experiments. , Therefore, there is plenty of room for exploration in operando surface chemistry for a robust foundation of future heterogeneous catalysis.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…Methoxy is an important reaction intermediate that adsorbs strongly on Cu surfaces, making it easy to detect. Another surface species that was observed in AP-XPS studies is formate (HCOO*). It is rather peculiar for formate to form in the absence of oxygen or water; we argued in our previous studies that this species might be related to external effects such as a compromised base pressure before the measurements or cross-contamination from previous experiments. ,, Such problems are common in shared user facilities, where most AP-XPS setups are located, due to constraints of the experimental schedule …”
Section: Introductionmentioning
confidence: 99%
“…Although both UHV studies and DFT calculations provide valuable information on the methanol–Cu interaction, they are not sufficient. Capturing important conceptual issues that come along with heterogeneous catalysis requires surface-sensitive spectroscopy experiments performed under ambient conditions. Within this context, several studies were performed to investigate the interaction of methanol vapor in the mbar pressure range with various Cu surfaces in the past few years using ambient-pressure X-ray photoelectron spectroscopy (AP-XPS), sum frequency generation (SFG), and high-pressure scanning tunneling microscopy (HP-STM) techniques. Unlike UHV studies, dry dehydrogenation of methanol into methoxy was observed even on high-coordinated surfaces. Two effects contribute to this difference; the equilibrium shifts at ambient conditions compared to UHV conditions, and nonzero chemical potentials help to overcome the kinetic barriers . Methoxy is an important reaction intermediate that adsorbs strongly on Cu surfaces, making it easy to detect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could arise from oxygenated hydro- carbon contaminants, 31 with the corresponding component in the O 1s region convoluted into the larger OH−H 2 O peak, although this could also be assigned to formate. 29 Notably, the O* peak in the O 1s spectrum (Figure 2c(iv)) is greatly diminished in intensity relative to the other adsorbed and gas phase peaks when compared to Figure 2c(iii). This decrease is consistent with CO scavenging O* from the catalyst surface to form gas phase CO 2 , i.e., shifting the equilibrium of dissociative CO 2 adsorption (CO 2 ⇌ O* + CO).…”
Section: ■ Experimental Methodsmentioning
confidence: 91%